2020
DOI: 10.1001/jamadermatol.2020.0079
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Lebrikizumab, a High-Affinity Interleukin 13 Inhibitor, in Adults With Moderate to Severe Atopic Dermatitis

Abstract: IMPORTANCE Interleukin 13 (IL-13) is a central pathogenic mediator driving multiple features of atopic dermatitis (AD) pathophysiology.OBJECTIVE To evaluate the efficacy and safety of lebrikizumab, a novel, high-affinity, monoclonal antibody targeting IL-13 that selectively prevents formation of the IL-13Rα1/IL-4Rα heterodimer receptor signaling complex, in adults with moderate to severe AD. DESIGN, SETTING, AND PARTICIPANTSA phase 2b, double-blind, placebo-controlled, dose-ranging randomized clinical trial of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
244
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(257 citation statements)
references
References 60 publications
6
244
0
7
Order By: Relevance
“…A second phase IIb trial in adults reported similar efficacy results (Table 1) [33]. In the TREBLE study, there were no life-threatening adverse events and no adverse events showed a dose-dependent trend [32].…”
Section: Lebrikizumabmentioning
confidence: 71%
“…A second phase IIb trial in adults reported similar efficacy results (Table 1) [33]. In the TREBLE study, there were no life-threatening adverse events and no adverse events showed a dose-dependent trend [32].…”
Section: Lebrikizumabmentioning
confidence: 71%
“…125 mg every 4 weeks (250 mg loading dose; n = 73), 250 mg every 4 weeks (500 mg loading dose; n = 80) or 250 mg every 2 weeks (500 mg loading dose at baseline and week 2; n = 75), while 52 patients received placebo. At week 16, the mean NRS pruritus score percentage changes were − 35.9%, − 49.6%, − 60.6%, and 4.3% of patients, respectively ( p = 0.05, p < 0.001 and p < 0.001 compared with placebo, respectively) [ 101 ].…”
Section: Biologic Drugsmentioning
confidence: 99%
“…Tralokinumab, an anti-IL-13 antibody, has shown promising results in a phase 2b study, with a very good safety profile while also being clinically effective [59]. Lebrikizumab a monoclonal antibody targeting IL-13 has shown promising results in a phase 2b study and has demonstrated a favorable safety profile [60]. All monoclonal antibodies share the advantage that drug-drug-interactions are not an issue in a patient population which is likely to use multiple medications.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Study data presented in congresses indicate a fast onset of the anti-pruritic and anti-inflammatory effects of the JAK inhibitors. The most important side effects of JAK inhibitors are a reactivation of viral infections, thrombosis, and pulmonary emboli which should be taken seriously (60).…”
Section: Expert Opinionmentioning
confidence: 99%